Ergonomic risk factors associated with muscuslokeletal disorders in computer workstation - Abdol Rahman, Mohd Nasrull; Masood, Ibrahim; Awalludin, Nur Farahanim; Hassan, Mohd Fahrul (Research India Publications, 2017)
Ergonomics Risk Factors (ERFs) at computer works are commonly related to Musculoskeletal Disorders (MSDs) such as repetitive movements, doing work in awkward postures and static postures while prolonged seating at works. The main objective of this study was to investigate the ergonomic risk factors associated with MSDs among employees in computer workstation. In this study, the data were obtained by structured interview using self-reported questionnaire and direct observation. The results show that there is significant association between neck and stress score with musculoskeletal symptoms and among office workers. As a conclusion, by assessing ERFs at workplace, the effectiveness of workplace interventions can be evaluated without waiting for changes in the prevalence of MSDs.